Hubungan Kepatuhan Diet Dash Dengan Asupan Natrium, Lemak Dan Kalium Pada Pasien Hipertensi Di Rawat Jalan Rs Muhammadiyah Palembang - Siti Soleha; Zairinayati (jurnal kesehatan terapan sains dan teknologi, 2024)
Data from the World Health Organization (WHO) shows that the incidence of hypertension in the world will increase every year and reach 29.2% in 2023. Dash diet compliance has factors that influence patient compliance, namely compliance in implementing the diet program related to understanding of instructions and knowledge. The DASH diet is a diet that recommends consuming low fat, low salt and increasing potassium intake to help lower blood pressure. To determine the relationship between compliance with the Dash diet and sodium, fat and potassium intake in patients with hypertension. This method uses a Semi Quantitative Form-FFQ questionnaire with an interview method. The number of subjects in this study were 60 hypertensive patients with heart complications. Results: There is a relationship between diet compliance and fat and sodium intake (p value < 0.05). There is no relationship between diet compliance and potassium intake (p value ≥ 0.05).